Intraoperative Red Blood Cell Transfusion Decision-making: A Systematic Review of Guidelines. Issue 1 (July 2021) - Baker, Laura; Park, Lily; Gilbert, Richard; Ahn, Hilalion; Martel, Andre; Lenet, Tori; Davis, Alexandra; McIsaac, Daniel I.; Tinmouth, Alan; Fergusson, Dean A.; Martel, Guillaume
Abstract : Objectives: The objective of this work was to carry out a systematic review of clinical practice guidelines (CPGs) pertaining to intraoperative red blood cell (RBC) transfusions, in terms of indications, decision-making, and supporting evidence base. Summary of Background Data: RBC transfusions are common during surgery and there is evidence of wide variability in practice. Methods: Major electronic databases (MEDLINE, EMBASE, and CINAHL), guideline clearinghouses and Google Scholar were systematically searched from inception to January 2019 for CPGs pertaining to indications for intraoperative RBC transfusion. Eligible guidelines were retrieved and their quality assessed using AGREE II. Relevant recommendations were abstracted and synthesized to allow for a comparison between guidelines. Results: Ten guidelines published between 1992 and 2018 provided indications for intraoperative transfusions. No guideline addressed intraoperative transfusion decision-making as its primary focus. Six guidelines provided criteria for transfusion based on hemoglobin (range 6.0–10.0 g/dL) or hematocrit (<30%) triggers. In the absence of objective transfusion rules, CPGs recommended considering other parameters such as blood loss (n = 7), signs of end organ ischemia (n = 5), and hemodynamics (n = 4). Evidence supporting intraoperative recommendations was extrapolated primarily from the nonoperative setting. There was wide variability in the quality of included guidelines based on AGREE II scores. Conclusion: This review has identified several clinical practice guidelines providing recommendations for intraoperative transfusion. The existing guidelines were noted to be highly variable in their recommendations and to lack a sufficient evidence base from the intraoperative setting. This represents a major knowledge gap in the literature. Abstract : Supplemental Digital Content is available in the text